Człowiek miarą Wszechświata? Problem zasad antropicznych w kosmologii - Łagosz, Marek (Filozofia Nauki, 2002)
The paper discusses problems concerning anthropocentric understanding of cosmology and physics. The author considers two version of anthropic principle ("weak" and "strong"). Among other things the connection between anthropic principle and cosmological principle is here analysed. The author also deals with the problem of object-subject relation in physical science (probability and measurement in quantum mechanics). He have come to the conclusion, that anthropocentric interpretation of physical science leads to essential difficulties.